PROFILE OF UNDERSTANDING THE CONCEPT OF STRAIGHT MOTION KINEMATICS IN STUDENTS OF SMAN 8 KOTA BENGKULU - Putri, Rany Utami; Syarkowi, Ahmad; Medriati, Rosane (Jurnal Pendidikan Matematika dan IPA, 2024)
Abstract This study aims to determine the understanding of the concept of straight motion kinematics at SMAN 8 Bengkulu City.   The research method used is the Cross-sectional Survey method, with data analysis techniques using descriptive analysis.   The sample in this study was class X students, amounting to 72 people with a sampling technique using Random Sampling.   The research instrument used is a multiple-choice test instrument, an indicator of concept understanding with valid criteria.   The test instrument already covers 3 aspects of understanding the concept.   From the results of the study, the average score of student concept understanding was 8.26 with the highest score of 14 and the lowest score of 3. The highest percentage in the aspect of understanding the concept was interpretation and extrapolation with the results of the average score of 33% in the medium category, while the   the lowest in the aspect of translation obtained an average score of 26% in the low category